Not too ugly to be tasty: Guiding consumer food inferences for the greater good. (September 2021) - Pfeiffer, Bruce E.; Sundar, Aparna; Deval, Hélène
Highlights: Consumers are unwilling to buy or eat suboptimal food, leading to food waste. Consumers find well-formed produce vs. deformed produce to be more aesthetically pleasing and this leads to more positive consumer inferences of taste, health, and quality. Consumer inferences contribute to perceptions of seller competence. The effects of form on consumer inferences may depend on different distribution channels (grocery vs. farmers market). Abstract: The issue of food waste is an important societal challenge with a significant environmental impact. An important issue contributing to food waste is consumers' unwillingness to purchase suboptimal food. Past literature has shown that people prefer perfectly formed food to abnormally shaped food when given a choice, but much of the mechanism underlying this preference is not well documented. Using a framework based on the halo effect, the authors focus on consumers affective and cognitive responses that cause them to shy away from produce that does not meet the usual aesthetic criteria. Results demonstrate that consumers find well-formed produce vs. deformed produce to be more aesthetically pleasing (beautiful) and that this positive affective reaction leads to more positive consumer inferences of taste, health, and quality. Results also indicate that consumers view sellers of well-formed produce to be more competent than sellers of deformed produce and that this perception is driven by perceptions of beauty and consumer inferences of taste, health, and quality. Lastly, results show that the effects of form on consumer inferences may depend on different distribution channels. Shopping at a farmers market mitigates the impact of the deformation on consumer inferences. Given that form and actual taste, health, and quality are not generally correlated, the results indicate that consumers are making inaccurate inferences. Exploring these inferences has the potential to open new avenues to educate consumers.